Croppie: AI-powered information extraction from natural language - García-Acosta, Sebastian (2024)
This report addresses the fundamental challenge of extracting key fields from natural language text in the context of natural language processing (NLP). Focusing on Spanish text, our solution, integrated into Croppie, offers an efficient and precise method for extracting essential information. Emphasizing robustness to colloquial expressions and grammatical errors, the report discusses implementation alternatives and presents the implemented solution, with the code available on our GitHub repository. This functionality is crucial for automated decision-making by enhancing the understanding of context in natural language conversations.